Keragaan F1 dan Heterosis Karakter Agronomis pada Beberapa Persilangan Padi Beras Merah - Muliarta Aryana, I Gusti Putu; Ketut Sudarmawan, Anak Agung; Santoso, dan Bambang Budi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Study on the effect of heterosis is important in order to find potential parent for creating a new superior variety. This research was aimed to study the phenotipic expression of F1 and heterosis on agronomics characters some crossed red rice. Experiment was done at a paddy field in Nyurlembang, West Lombok, West Nusa Tenggara during August–November 2016, and it was arranged in a randomized block design of 12 genotypes as treatment with five replications. Genotypes evaluated were Fatmawati, IPB3S, G9(F2BC4P19-36), F1-Fatmawati/Inpago Unram-I, F1-Fatmawati/G9, F1-IPB 3S/Inpago Unram-I, F1-IPB 3S/G9, F1-Inpago Unram-I/Fatmawati, F1-G9/Fatmawati, F1-Inpago Unram-I/IPB 3S, and F1-G9/IPB 3S. The results showed that based on the F1 phenotipic performances and heterosis on grain weight per hills, yield, 1000 grain weight, number of grain per panicle, length of panicle, number of productive tiller per hill, and time of flowering, there were three genotypes that had a semi ideal type of red rice with high yield potential. The genotypes were F1-Fat/G9, F1-Inpago Unram-I/IPB 3S, and F1-IPB 3S/Inpago Unram-I.Keywords: diversity, agronomic, yield, red rice